2018
DOI: 10.1159/000489401
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-Lymphocyte Ratio Predicts Functional and Safety Outcomes after Endovascular Treatment for Acute Ischemic Stroke

Abstract: Background and Objective: Endovascular treatment (EVT) is proven to be safe and effective for treating acute large vessel occlusion stroke (LVOS). The neutrophil-lymphocyte ratio (NLR) reflects systemic inflammation, which plays an important role in the process of treating ischemic stroke. This study aims to explore the relationship between NLR and the clinical outcomes of LVOS patients undergoing EVT. Methods: Patients were selected from the EVT for acUte Anterior circuLation (ACTUAL) ischemic stroke registry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 30 publications
1
53
0
Order By: Relevance
“…Clinical evidences have shown that, in AIS patients, high NLR levels are associated with increased infarct volume and mortality (Celikbilek, Ismailogullari, & Zararsiz, 2014;Gökhan et al, 2013;Tokgoz et al, 2013). Furthermore, NLR is a predictor of recurrent ischemic stroke and 90-day poor functional outcome in AIS patients receiving endovascular stroke therapy or IVT or antiplatelet medications (Brooks et al, 2014;Duan et al, 2018;Malhotra et al, 2018;Qun et al, 2017). In the present study, it is the first time to investigate the relationship between NLR and early functional deterioration in AIS patients with IVT therapy.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Clinical evidences have shown that, in AIS patients, high NLR levels are associated with increased infarct volume and mortality (Celikbilek, Ismailogullari, & Zararsiz, 2014;Gökhan et al, 2013;Tokgoz et al, 2013). Furthermore, NLR is a predictor of recurrent ischemic stroke and 90-day poor functional outcome in AIS patients receiving endovascular stroke therapy or IVT or antiplatelet medications (Brooks et al, 2014;Duan et al, 2018;Malhotra et al, 2018;Qun et al, 2017). In the present study, it is the first time to investigate the relationship between NLR and early functional deterioration in AIS patients with IVT therapy.…”
Section: Discussionmentioning
confidence: 67%
“…Neutrophil, the main inflammatory cell of AIS, on one hand, can release free oxygen radicals propagating secondary brain injury in penumbra regions (Ceulemans et al, 2010 TA B L E 5 (Continued) (Continues) neutrophils are the source of matrix metalloproteinase-9 (MMP-9), which can directly result in blood-brain barrier (BBB) breakdown and hemorrhagic transformation (Duan et al, 2018). These may be significant contributors in the occurrence of END.…”
Section: Discussionmentioning
confidence: 99%
“…Of the remaining 26 articles, 19 were removed due to being reviews ( n = 3) and not reporting relevant outcomes ( n = 16). Seven articles were eventually included in our meta‐analysis (Duan et al, ; Goyal et al, ; Guo et al, ; Maestrini et al, ; Malhotra et al, ; Pikija et al, ; Song et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that the NLR is independently associated with clinical outcomes and short‐term mortality in patients with AIS (Gokhan et al, ; Tokgoz, Keskin, Kayrak, Seyithanoglu, & Ogmegul, ; Yu et al, ; Zhang et al, ). In addition, it was reported that a higher admission NLR is an independent risk factor for HT and 3‐month functional outcome in patients with AIS both with and without reperfusion therapy (Duan et al, ; Goyal et al, ; Guo et al, ; Maestrini et al, ; Pikija et al, ; Song et al, ). The subject of our study was to comprehensively summarize the value of NLR for predicting HT in patients with AIS by performing a meta‐analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies suggested that inflammatory mediators have significant clinical significance in AIS and HT [6,7]. Neutrophil-to-lymphocyte ratio (NLR) is a rather new risk determinant factor of the inflammatory response that has been shown to be associated with the severity and prognosis of cardiovascular events, ischemic stroke, cancer, and bacterial infectious disease [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%